2005
DOI: 10.1073/pnas.0408932102
|View full text |Cite
|
Sign up to set email alerts
|

Dual oxidase 1-dependent MUC5AC mucin expression in cultured human airway epithelial cells

Abstract: Mucus hypersecretion is a prominent manifestation in patients with chronic inflammatory airway diseases. MUC5AC mucin is a major component of airway mucus, and its expression is modulated by a TNF-␣-converting enzyme (TACE)-EGF receptor pathway that can be activated by reactive oxygen species (ROS). Dual oxidase 1 (Duox1), a homologue of glycoprotein p91 phox , is expressed in airway epithelium and generates ROS. We hypothesize that Duox1 activates TACE, cleaving pro-TGF-␣ into soluble TGF-␣, resulting in muci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
225
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(245 citation statements)
references
References 30 publications
18
225
1
1
Order By: Relevance
“…Various studies have suggested that MMPs and ADAMs can be activated by oxidants or by NO/SNO, which is suggested to involve oxidation and/or S-nitrosylation of the prodomain cysteine residue [137][138][139], although this is generally supported by indirect evidence. Biochemical analysis of oxidative activation of purified MMPs has shown that NO or H 2 O 2 are ineffective at directly activating these proteases, but they can be activated by more potent oxidants such as HOCl or ONOO − [140,141].…”
Section: Regulation Of Proteasesmentioning
confidence: 99%
“…Various studies have suggested that MMPs and ADAMs can be activated by oxidants or by NO/SNO, which is suggested to involve oxidation and/or S-nitrosylation of the prodomain cysteine residue [137][138][139], although this is generally supported by indirect evidence. Biochemical analysis of oxidative activation of purified MMPs has shown that NO or H 2 O 2 are ineffective at directly activating these proteases, but they can be activated by more potent oxidants such as HOCl or ONOO − [140,141].…”
Section: Regulation Of Proteasesmentioning
confidence: 99%
“…Moreover, the airway epithelium also generates airway mucins that facilitate mucociliary clearance of inhaled particulates or microorganisms (103,104). Recent studies suggest that DUOX may participate in these responses as well, as illustrated by DUOX1-mediated production of epithelial mucins, such as MUC1 and MUC5AC, in response to inflammatory mediators such as neutrophil elastase or tumor necrosis factor (TNF)-α (105,106). Similarly, DUOX1 also mediates epithelial production of the neutrophil chemokine IL-8 in response to stimulation by bacterial lipopolysaccharide (LPS) (107).…”
Section: Functions Of Epithelial Duox: Host Defense and Intracellularmentioning
confidence: 99%
“…4. Critical to the activation of these signaling pathways is the proteolytic cleavage of membrane-associated EGFR ligands by cell surface proteases, such as TNFα-converting enzyme (TACE; ADAM17), a member of the a disintegrin and metalloproteinase (ADAM) family of metzincin metalloproteinases (105,108,121), and matrix metalloproteinases (MMPs) such as gelatinase B (MMP-9), which play critical roles in epithelial host defense and in epithelial repair in response to injury (104,122,123). An important common structural and functional feature shared by the ADAM/MMP proteases is the presence of an invariant cysteine-containing pro-domain, which maintains latency by ligating the active site Zn 2+ , and is susceptible to oxidative disruption (124)(125)(126)(127).…”
Section: Functions Of Epithelial Duox: Host Defense and Intracellularmentioning
confidence: 99%
See 2 more Smart Citations